Keanekaragaman Jenis Plankton di Sungai Desa Tompobulu Kabupaten Maros - Abbas, Ahmad Ashar; Hasbi, Ibnu Malkan (Jurnal Riset Diwa Bahari (JRDB), 2024)
Plankton can be grouped into two, namely phytoplankton and zooplankton. The phytoplankton group is autotrophic so that it acts as a primary producer in the waters. The research location is in Tompobulu Village, Maros Regency. Data collection was taken in June 2024. The temperature at the station based on the measurement results at the station is 28°C, pH value 7.4, total suspended solids value (TSS) 51 mg/l, do (Dissolved oxygen) value 4 mg/l. The data calculated is the index of diversity, uniformity and dominance. Overall findings of this study showed: Diversity index 1,42, uniformity 0,34 and dominance index 0,38 . Plankton sampling stations show that there are 12 species of plankton, namely: Amphora sp, Cocconeis sp, Coscinodiscus sp., Cymbella sp., Gyrosigma sp., Licmophora sp., Navicula sp., Pediastrum sp., Pinnularia sp., Surirella sp. Synedra sp.1, Synedra sp.2. It can be seen from the data above that the highest cell/liter value with a value of 1,130 is Navicula sp. The lowest value of 10 cells/liter is 4 species, namely: Pediastrum sp, Amphora sp, Coscinodiscus sp and Licmophora sp. The conclusion of the study is that the level of plankton diversity in the Tompobulu river is classified as moderate with a value of 1.42, the most abundant species is Navicula sp with a total of 1130 cells/liter. The water condition that affects and does not meet the quality standards is TSS. This parameter is also what affects the condition of the plankton.